1996
DOI: 10.1111/j.1460-9568.1996.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

The Projections of the Lateral Reticular Nucleus to the Deep Cerebellar Nuclei. An Experimental Analysis in the Rat

Abstract: The projections of the lateral reticular nucleus (LRN) to the cerebellar nuclei were studied using the retrograde axonal transport of tetramethyl rhodamine dextran amine (10% solution in 0.01 M neutral phosphate buffer) in 19 adult Wistar strain rats. The cerebellar nuclei receive topographically organized projections from the LRN. The projections are bilateral with an ipsilateral predominance and they are symmetrical. The contralateral component is progressively larger for projections to the nuclei interposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…This result is partly consistent with the retrograde labeling study by Parenti et al (1996). They showed that the DN received a projection from the dorsomedial part of the rostral LRN, into which we could not inject BDA, and distinguished the intermedioventral and caudal LRN and dorsolateral part of the middle LRN, with the former projecting to the FN and the latter to the IP.…”
Section: Area-dependent or Neuron-dependent Differences In Lrn Projecsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is partly consistent with the retrograde labeling study by Parenti et al (1996). They showed that the DN received a projection from the dorsomedial part of the rostral LRN, into which we could not inject BDA, and distinguished the intermedioventral and caudal LRN and dorsolateral part of the middle LRN, with the former projecting to the FN and the latter to the IP.…”
Section: Area-dependent or Neuron-dependent Differences In Lrn Projecsupporting
confidence: 92%
“…Previous anterograde or retrograde studies did not identify whether nuclear projections of LRN neurons are by means of collaterals of mossy fibers or if there are specific nuclear-projecting neurons. Because most of the reconstructed LRN axons originated from the LRNm, we cannot discuss in detail the topographical relationship in LRN-nuclear projection as elaborated in a retrograde labeling study (Parenti et al, 1996). However, it is very clear that the topographical relationship in LRN-nuclear projection was much weaker and vaguer than that in the olivonuclear projection (Van der Want et al, 1989;Sugihara et al, 1996), in which neurons in a subdivision of the IO project to a relatively localized area in one of the cerebellar nuclei.…”
Section: Characteristics Of the Projection Of Single Axons Of Lrn Neumentioning
confidence: 98%
See 1 more Smart Citation
“…The lateral reticular nucleus of the rat has been reported to project to almost all lobules of the cerebellum, with an ipsilateral preponderance (Chan- Palay, 1977;Eisenman, 1982;Hrycyshyn et al, 1982;Payne, 1987;Parenti et al, 1996). In the anterograde axonal Chockkan, V., & Hawkes, R. (1994).…”
Section: Lateral Reticular Nucleusmentioning
confidence: 97%
“…Projection patterns of single mossy fibers originating from the lateral reticular nucleus in the rat cerebellar cortex and nuclei. Journal of Comparative Neurology 411, 97-118 with permission, Copyright 1999, Wiley-Liss, Inc. collateral projections that terminate predominantly ipsilaterally Parenti et al, 1996;Wu et al, 1999).…”
Section: Lateral Reticular Nucleusmentioning
confidence: 98%